2016
DOI: 10.1097/md.0000000000002915
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Multicenter Reference Interval Study for 28 Common Biochemical Analytes in China

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
10
31
1
Order By: Relevance
“…Thus, we recommend establishing gender-specific RIs for GGT (r p = -0.330). This study revealed that age-or gender-specific RIs are unnecessary for K, Na, Cl, Ca, and IP, as no clinically significant differences were observed, which is consistent with the results of previous studies (17)(18)(19)(20)(21)(22)(23). Based on the results described above, the RIs of common biochemical analytes were established in this study, most of which were significantly narrower than those listed in the WS/T 404 (18)(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we recommend establishing gender-specific RIs for GGT (r p = -0.330). This study revealed that age-or gender-specific RIs are unnecessary for K, Na, Cl, Ca, and IP, as no clinically significant differences were observed, which is consistent with the results of previous studies (17)(18)(19)(20)(21)(22)(23). Based on the results described above, the RIs of common biochemical analytes were established in this study, most of which were significantly narrower than those listed in the WS/T 404 (18)(19)(20)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…This helps avoid exaggerated SDR for the actual narrow range of RIs or masked differences caused by the interaction between the factors. [2,21] In effect, no sex difference for all analytes was detected , which was consistent with data in different regions [8,17,22].…”
Section: Age-dependent Ris For 26 Common Biochemical Analytessupporting
confidence: 90%
“…Despite the well standardized measurements of major laboratory test, it is di cult to establish harmonized and uniform RIs on a global scale. Previous research has found that the differences in RIs of analytes are due to their complex patterns of biological sources of variations, such as region, race, diet, and more individual characteristic [1,2]. Data from the studies we have published con rms that establishing age-and sexappropriate local RIs is more accurate and reliable for providing clinical decision support, especially in pediatrics [3][4][5][6].…”
Section: Introductionmentioning
confidence: 85%
“…In this study, we observed a similar association of BMI with those nutritional/inflammatory markers, but at much weaker degree: i.e., values of |rp| for ALT, CRP, GGT, and TG were all below 0.2. For TC, UL of Egyptians was 6.28 mmol/L for both sexes <45 years, comparable to other studies: Turkey 6.2(11), India 6.2(10), Saudi Arabia 6.36(12) and China 6.16 mmol/L(13),…”
Section: Discussionsupporting
confidence: 89%